2008
DOI: 10.1118/1.2963990
|View full text |Cite
|
Sign up to set email alerts
|

Use of a two‐dimensional ionization chamber array for proton therapy beam quality assurance

Abstract: Two-dimensional ion chamber arrays are primarily used for conventional and intensity modulated radiotherapy quality assurance. There is no commercial device of such type available on the market that is offered for proton therapy quality assurance. We have investigated suitability of the MatriXX, a commercial two-dimensional ion chamber array detector for proton therapy QA. This device is designed to be used for photon and electron therapy QA. The device is equipped with 32 x 32 parallel plate ion chambers, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 12 publications
1
75
1
Order By: Relevance
“…Arjomandy et al ( 5 ) investigated the use of a high‐resolution 2D ion chamber array for periodic proton beam QA and found that it was appropriate for checking proton beam flatness and symmetry, as well as dose output. However, considering factors such as cost, end‐user training, equipment setup time, and complexity of data interpretation, we believe that high‐resolution 2D arrays are more suitable for monthly and annual QA rather than daily QA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arjomandy et al ( 5 ) investigated the use of a high‐resolution 2D ion chamber array for periodic proton beam QA and found that it was appropriate for checking proton beam flatness and symmetry, as well as dose output. However, considering factors such as cost, end‐user training, equipment setup time, and complexity of data interpretation, we believe that high‐resolution 2D arrays are more suitable for monthly and annual QA rather than daily QA.…”
Section: Discussionmentioning
confidence: 99%
“…Some properties of proton beams do not have equivalence in photon therapy, which requires a novel approach to designing efficient QA device and the corresponding workflow. Based on recommendations by various task groups and other studies, ( 1 5 ) our daily QA process tests the safety, image‐guided patient position system, and reference proton beam characteristics (output, range, and symmetry). Table 1 is a summary of our daily QA procedures and their corresponding tolerances.…”
Section: Introductionmentioning
confidence: 99%
“…It provides an accuracy in dose measurements of ∼1% (Ref. 23) and a spatial resolution of ∼1 mm when bilinear interpolation of raw data is performed. All the irradiations were performed with the nozzle in vertical position (gantry at 0…”
Section: B3 Two-dimensional Dose Profile Measurements and Simulatmentioning
confidence: 99%
“…The 2D dose distributions at specific depths were measured with a 2D ion chamber array (MatriXX PT, IBA Dosimetry GmbH, Germany) [23]. More details of the measurements and the experimental uncertainties are described in the references [21][22][23].…”
Section: Measurementsmentioning
confidence: 99%